The Antagonism between Secular Elites and Refugees in the context of “Theological-Political Predicament”: The Case of Turkey - Günsoy, Funda; Turowski, Mariusz (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
In this paper, we argue that the refugees serve as the founding uncertainty within the process of “normalization (and normization) of the exception” through non-spatialization or broadening of the perception of threat in accordance with friend-enemy distinction. At the same time, they are used as a weapon that makes legitimate interventions by the sovereign who converts the current crisis into a permanent situation. In the case of Turkey, the determinant in both the antagonism and the friendship towards Syrian refugees is their identity based on a property of being Arabian Muslims. In this framework, we will argue that the resentments towards Syrian refugees by secularist/Kemalist circles can be treated as an example of the eternal problem in the context of Straussian concept of the “theological-political predicament”.
Keywords: Leo Strauss; Carl Schmitt; Alain Badiou; Turkey; secularism; religion